Certified and Non-Certified Teachers’ Performance in Jombang Religious-Cultural Regency - Imron Muttaqin (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
This study aimed to investigate the performance of teachers who have been certified and those who have yet to be in professional teacher certification programs in Jombang Regency East Java Province. The type of research is quantitative. Data were collected using questionnaires and a Likert scale with 5 answer choices. Data analysis was performed using a t-test for independent samples using SPSS. The respondent comprised 370 teachers, including 185 professional and 185 non-professional certified teachers. The findings revealed a difference in performance between certified and non-certified teachers. Teachers who have been certified perform better than teachers who have not. Based on the present study's findings, it is suggested that the government maintain teacher certification, with continuous improvement and innovation for better development. This research has implications for the government that teacher certification programs and policies are still worth for continuing, although they need to be enriched with innovation and creativity, technological developments, stakeholder needs, and strengthening religious culture.